2015
DOI: 10.3390/molecules200711733
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence of Quinone Methides in Asymmetric Organocatalysis

Abstract: Quinone methides (QMs) are highly reactive compounds that have been defined as "elusive" intermediates, or even as a "synthetic enigma" in organic chemistry. Indeed, there were just a handful of examples of their utilization in catalytic asymmetric settings until some years ago. This review collects organocatalytic asymmetric reactions that employ QMs as substrates and intermediates, from the early examples, mostly based on stabilized QMs bearing specific substitution patterns, to more recent contributions, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(56 citation statements)
references
References 60 publications
(73 reference statements)
1
53
0
Order By: Relevance
“…o ‐Quinone methides are novel and powerful motifs used in organic synthesis . ( R )‐3,3′‐dibromo‐BINOL ( R )‐ 49 was found to catalyze the addition of arylboronates as 48 to the benzylic position of ortho ‐quinone methide 47 to yield ortho substituted phenols 50 with er higher than 90:10 (Scheme ) .…”
Section: Asymmetric Organocatalytic 14‐additionsmentioning
confidence: 99%
“…o ‐Quinone methides are novel and powerful motifs used in organic synthesis . ( R )‐3,3′‐dibromo‐BINOL ( R )‐ 49 was found to catalyze the addition of arylboronates as 48 to the benzylic position of ortho ‐quinone methide 47 to yield ortho substituted phenols 50 with er higher than 90:10 (Scheme ) .…”
Section: Asymmetric Organocatalytic 14‐additionsmentioning
confidence: 99%
“…[9,10] Ortho-quinone methides (o-QMs) feature a particularly reactive 4p-system and have increasingly been exploited as versatile synthetic intermediates for the construction of complex heterocycles. [11] In recent years, we and others have meticulously developed Brønsted acid catalyzed reactions of o-QMs with a wide range of typically 2p-nucleophiles, leading to a broad range of benzannulated oxygen heterocycles with good to excellent stereocontrol. [12,13] We now report the first cooperative, catalytic, enantioselective [4+3]-cycloannulation of o-QMs and carbonyl ylides to afford complex and enantiomerically highly enriched oxabicyclic dibenzooxacines.…”
mentioning
confidence: 99%
“…It has been reported that the introductiono fs terically demanding groups at this positionl eads to the preferred formation of the (Z)-quinone methides, whereas unsubstituted derivatives mainly form E isomers. [14] We thusr ationalised that this lower selectivity mayb ea ttributed to formation of al ess selective (Z)-quinone methide (or an E/Z mixture) in theset wo cases.…”
Section: Development Of An Enantioselective Reaction Protocolmentioning
confidence: 89%
“…[4-6, 12, 13] One particularly powerful methodology for the generation of carbo-and heterocyclic targets through [4+ +n]a nnulation approaches relies on the use of in situ generated o-quinone methides or analogousa za-o-quinonem ethides. [14,15] Recently, the first example of the use of in situ generated o-quinone methides 3 (precursor 1)f or [4+ +1] annulation reactions with in situ generated carbonyl-stabilised sulfur ylides 4 (obtained from sulfonium salts 2)t oa ccess 2,3-dihydrobenzofurans 5 was reported by Zhou and co-workers( Scheme 1). [5a] High yields and excellent diastereoselectivities were obtained fordifferent carbonyl-stabiliseds ulfur ylides.…”
Section: Introductionmentioning
confidence: 99%